Demeaning, depriving, and isolating the academic subject: A case study of the degradation of professional autonomy - Hartz, Ronald (Management learning, 2024)
This article explores the dismantling of professional autonomy during a change management programme at a business school in the United Kingdom. The change programme proposed the disinvestment from research in Critical Management Studies (CMS) and Political Economy and resulted in compulsory redundancies. The study reconstructs the managerial processing of this ‘case for change’ with a particular focus on the mechanisms behind the dismantling of professional autonomy. Specifically, three mechanisms of degradation are highlighted: first, a managerial attitude of censorship and anti-intellectualism that serves to demean academic scholarship, second, the regulation of time, space and information that deprives academics of the means to defend themselves and, finally, the isolation of professionals and the creation of docile academic subjects. By focussing on the micro-physics of power and understanding the mundane processes through which it takes effect and circulates, the ways in which it routinely undermines the autonomy of those it wants out, the article offers further avenues to discuss ways to resist the dismantling of professional autonomy in the managerial university.